PENGAWASAN PEDAGANG KAKI LIMA DI PASAR HONGKONG KOTA SINGKAWANG - Amir E.01108130, Muslich (FISIP Universitas Tanjungpura, 2013)
This study is written because researchers found strong phenomena are still many street vendors selling on the road, as well as the indication of the lack of supervision of market vendors in hongkong market. This study aims to determine the direct supervision and indirect supervision in hongkong market. Information retrieval techniques through interviews with informants and observations and documentation at location. informant of this study is Singkawang Government officials and some street vendors who are in Hong Kong Market.The results of this study were the direct supervision consisting of inspection, observations and reports in place while the indirect supervision with written reports and oral statements. The conclusion of this research is conducted Disperindag Supervision and Markets Unit is not maximized because the direct supervision performed 1 time in a year, while the indirect supervision of a more focused between leaders and subordinates within the agency. Suggestions from this study was the direct supervision conducted Disperindag and Markets Unit should be performed routinely, while the indirect supervision via oral report should report the conditions that actually occur in the field without the addition or subtraction of information. Keyword: Supervision, direct supervision, indirect supervision and Street Vendors